2018
DOI: 10.1186/s13046-018-0972-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia potentiates gemcitabine-induced stemness in pancreatic cancer cells through AKT/Notch1 signaling

Abstract: BackgroundProfound chemoresistance remains an intractable obstacle in pancreatic cancer treatment. Pancreatic cancer stem cells (CSCs) and the ubiquitous hypoxic niche have been proposed to account for drug resistance. However, the mechanism involved requires further exploration. This study investigated whether the hypoxic niche enhances gemcitabine-induced stemness and acquired resistance in pancreatic cancer cells by activating the AKT/Notch1 signaling cascade. The therapeutic effects of blockading this sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 44 publications
2
46
0
Order By: Relevance
“…Thus, ATRA is likely to target as yet unrecognized elements of the pathway laying downstream of the NOTCH1 protein in MB-157 cells. Given the role played by NOTCH proteins in the control of Epithelial-to-Mesenchymal-Transition (EMT) (43)(44) and the homeostasis of cancer stem-cells (10) , (45) (46), it is likely that ATRA down-modulates both processes (47) , (48) , (49). This is consistent with the differentiating effect of the retinoid and it may result in a reduction of the cancer stem-cell component of mammary tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ATRA is likely to target as yet unrecognized elements of the pathway laying downstream of the NOTCH1 protein in MB-157 cells. Given the role played by NOTCH proteins in the control of Epithelial-to-Mesenchymal-Transition (EMT) (43)(44) and the homeostasis of cancer stem-cells (10) , (45) (46), it is likely that ATRA down-modulates both processes (47) , (48) , (49). This is consistent with the differentiating effect of the retinoid and it may result in a reduction of the cancer stem-cell component of mammary tumours.…”
Section: Discussionmentioning
confidence: 99%
“…SOX2 is one of the key members of the SOX family gene and plays a critical role in the maintenance of the self-renewal and pluripotency of embryonic stem cells (44). Studies have revealed that SOX2 is an oncogene known to be ampli ed and overexpressed in carcinogenesis, metastasis and recurrence in many cancer types (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…HIFs are composed of an alpha (HIF-α) and a beta (HIF-β) subunit, and the oxygen-dependent HIF-α subunit is the key protein determining the transcriptional activity of HIFs, while the HIF-β subunit is structurally expressed in the cell nucleus (19). A large number of reports have revealed that oxygen deficit induces the generation of HIFs in human embryonic stem cells (hESCs), which have the ability to activate the Wnt and Notch self-renewal signaling pathways (20,21) and vascular endothelial growth factors (VEGFs) so that HIFs can maintain cells in an undifferentiated state and promote tumor vessel formation (22). MicroRNAs (miRNAs or miRs) are small noncoding single-stranded RNAs with a length of 22 nucleotides that affect the regulation of posttranscriptional gene expression (23).…”
Section: Microrna-137 Exerts Protective Effects On Hypoxia-induced Cementioning
confidence: 99%